2019
DOI: 10.3389/fimmu.2019.01415
|View full text |Cite
|
Sign up to set email alerts
|

An Historical Overview: The Discovery of How NK Cells Can Kill Enemies, Recruit Defense Troops, and More

Abstract: Natural killer (NK) cells were originally defined as effector lymphocytes of innate immunity characterized by the unique ability of killing tumor and virally infected cells without any prior priming and expansion of specific clones. The “missing-self” theory, proposed by Klas Karre, the seminal discovery of the first prototypic HLA class I-specific inhibitory receptors, and, later, of the Natural Cytotoxicity Receptors (NCRs) by Alessandro Moretta, provided the bases to understand the puzzling behavior of NK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 245 publications
(202 reference statements)
0
55
0
Order By: Relevance
“…Here we had the opportunity to evaluate patients admitted to hospital because of moderate to severe COVID-19 interstitial pneumonia and compared them to a small group of SARS-CoV-2 negative pneumonia and healthy We showed that patients with COVID-19 had a relative expansion of mature adaptive NK cells endowed with ADCC function, which was increased in this setting in line with ndings in other viral infections, particularly cytomegalovirus [6]. Other phenotypic features were compatible with a dysfunctional NK cell phenotype, namely the reduced frequencies of Siglec-7-, NKG2D-and NKp30expressing cells [8,9]. A recent study addressed the kinetics and breadth of immune responses associated with clinical resolution of COVID-19 in a single patient with relatively mild disease [10].…”
Section: Introduction Results and Discussionmentioning
confidence: 58%
“…Here we had the opportunity to evaluate patients admitted to hospital because of moderate to severe COVID-19 interstitial pneumonia and compared them to a small group of SARS-CoV-2 negative pneumonia and healthy We showed that patients with COVID-19 had a relative expansion of mature adaptive NK cells endowed with ADCC function, which was increased in this setting in line with ndings in other viral infections, particularly cytomegalovirus [6]. Other phenotypic features were compatible with a dysfunctional NK cell phenotype, namely the reduced frequencies of Siglec-7-, NKG2D-and NKp30expressing cells [8,9]. A recent study addressed the kinetics and breadth of immune responses associated with clinical resolution of COVID-19 in a single patient with relatively mild disease [10].…”
Section: Introduction Results and Discussionmentioning
confidence: 58%
“…In cancer patients, NK cells frequently display an impaired function (6,27). Thus, primary strategies in immunotherapy are aimed to boost in vivo NK cell-mediated antitumor activity.…”
Section: Boosting In Vivo Nk Cells With Immune Stimulatory Cytokinesmentioning
confidence: 99%
“…Although NK cells display a potent anti-tumor activity and are thought to participate to the control of tumor growth and metastatic spread, the tumor microenvironment may sharply inhibit their effector functions (4,5). This inhibitory effect is due to the tumor cells themselves as well as to other cells present in the tumor microenvironment and frequently involves both the downregulation of activating surface receptors and the de novo expression of inhibitory checkpoints (primarily PD-1) (6,7). In this contribution, we will briefly discuss different therapeutic strategies (Table 1), which allow to successfully exploit NK cell-mediated anti-tumor activity as well as novel promising approaches that may offer important new tools in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Control of NK cell functions: NK cells: kill susceptible targets, functionally interact with different immune cells, sense pathogens using certain Toll-like receptors (TLRs), adapt their responses to the local environment, and mount some degree of immunological memory [53]. Several elements in cell metabolism such as: glucose-driven glycolysis, and oxidative metabolism play critical roles in NK cell development, education, memory generation, and antitumor as well as antiviral effector functions [54].…”
Section: Nk Cell Function and Dysfunctionmentioning
confidence: 99%